Promoting Health through Accessible Public Playgrounds - Mehrnoosh Movahed; Luca Martial; Tiiu Poldma; Monica Slanik; Keiko Shikako (MDPI AG, 2023)
Every child, irrespective of socioeconomic status, ethnicity, or ability, deserves the fundamental right to experience play, which is a powerful and enriching activity that fosters their physical and mental health. Regrettably, most public play spaces hinder the complete inclusion of children with disabilities, with the main reason being a lack of universal accessibility. This study identified existing international and Canadian policies and community best practices related to inclusive playgrounds, and gathered stakeholders' opinions on the present condition of playgrounds, including challenges faced by children with disabilities and recommendations to make playgrounds inclusive. The questionnaires were completed by 97 participants. In addition, 10 individual interviews and three focus groups were performed. Ten policy documents and five community best practices were found. Our investigation identified factors that influence the design and implementation of inclusive playgrounds, categorized into three main areas: physical, social, and political environments. The results indicate that children with disabilities lack opportunities to engage fully in the physical and social aspects of playgrounds and spontaneous play activities with their peers. Notably, children with multiple disabilities may not feel welcomed or included in existing public play spaces.